ANALISIS PENERAPAN LITERASI DIGITAL DALAM MENCIPTAKAN KEMANDIRIAN BELAJAR SISWA HINDU DI MASA PANDEMI COVID 19 - Dewa Kadek Sudyana; Ni Made Surawati (UNHI PRESS, 2021)
The emergence of a virus known as Covid-19, which is known to have a very high transmission rate, has spread so quickly to several countries around the world that it has forced several countries to implement policies to lockdown and organize online learning in order to prevent the spread of the Covid-19 virus. By implementing online learning strategies, students absolutely need digital literacy skills. This is because it is impossible to apply online learning without the support of high digital literacy. Students with good learning independence will always seriously study the subject matter provided by the teacher even though they are at home. High learning independence will make students willing to learn on their own